Red Cell Distribution Width (RDW) and Hb% in the Detection of Iron Deficiency Anemia in Pregnant Women (Anwer Khan Modern Medical College Journal, 2018)
Background: Detection of iron deficiency early during pregnancy is essential for correct management. Red cell distribution width (RDW) is a new routine parameter in fully automated hematology analyzer that can give the idea of early iron deficiency before Hb%. This study was aimed to see the role of red cell distribution width and Hb% in determining early iron deficiency in pregnant women.Methods: In this study 190 pregnant women were included. CBC including Hb% and RDW and iron profile were done. RDW were compared with Hb% in various stages of iron deficiency.Results: RDW was more significant than Hb level in latent iron deficiency when Hb level was normal (p